Como a utilização do leilão reverso eletrônico pode impactar as compras do setor hoteleiro brasileiro - Conceição, Ronaldo Caitano da (2006)
Globalization, as an economic, social and cultural phenomenon, has profoundly changed the behavior of individuals, companies and nations. It is responsible for an increasingly borderless world and a significant increase in competition between companies, due to the rapid dissemination of information and technical and scientific advances. Every day at the global level, the growing competition between companies makes it more difficult for corporations to boost their earnings through added revenues, which makes it imperative to cut costs to be profitable. To this end, utilization of the reverse auction, which has emerged as a new purchasing tool in recent years, offers the possibility of a significant and immediate reduction in prices, as well as greater operational efficiency in purchasing. The Brazilian hotel industry has also experienced transformations with globalization. A business characterized in the 70s by small and medium-sized companies has developed into an economic segment that today includes large international chains and, therefore, also needs to cut costs to be profitable. Applying the case study approach, this research seeks to evaluate the impact that the utilization of a reverse auction as a purchasing tool has had on the hotel industry in Brazil.